Sources of change in Mexican agricultural production, 1940-65 - Hertford, Reed (Washington D. C. Economic Research Services, U.S. Department of Agriculture, 1971)
The publication is a product of a Ph.D. dissertation, titled Sources of increase in Mexican agricultural production, 1940-65. It examines agricultural production, in Mexico from 1940 to 1965.
Bibliography: leaves 100-102.
lje 04/07/17
Loans
Keywords: Agriculture- Mexico; Agricultural productivity; Technological progress; Irrigation and land reform; Crop yield; Mexico